1976
DOI: 10.1097/00000658-197604000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alpha and Beta Adrenergic Blockade on Epinephrine Induced Pulmonary Insufficiency

Abstract: Recent studies demonstrated that epinephrine causes significant pulmonary A-V shunting. This study reports the effect of alpha and beta adrenergic blockade on this shunting. Sixty-three anesthetized mongrel dogs were ventilated with a mechanical respirator. Measurements of (1) the pulmonary shunt, (2) cardiac output, (3) mean pulmonary artery, pulmonary capillary wedge and systemic pressures, and (4) pulmonary and systemic vascular resistances were obtained at 5, 15 and 30 minute intervals during the first hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Berk et al 15 and others 16,17 theorized that shunt during prolonged epinephrine infusion was initially due to pulmonary arterial flow redistribution with secondary ventilation-perfusion inequalities and that only after several hours was it caused by interstitial and alveolar edema. They ascribed these effects to β -adrenergic stimulation as they were reversed by propranolol whereas phenoxybenzamine pretreatment had only minor protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Berk et al 15 and others 16,17 theorized that shunt during prolonged epinephrine infusion was initially due to pulmonary arterial flow redistribution with secondary ventilation-perfusion inequalities and that only after several hours was it caused by interstitial and alveolar edema. They ascribed these effects to β -adrenergic stimulation as they were reversed by propranolol whereas phenoxybenzamine pretreatment had only minor protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, using 15-to 30-m radioactive albumin microspheres, Nomoto et al (40) demonstrated that IPAVA open in dogs infused with EPI. Additionally, Berk and colleagues also suggested a direct effect of EPI increasing venous admixture in anesthetized dogs based on an immediate fall in arterial partial pressure of oxygen (PO 2 ) during EPI infusion (2)(3)(4), while Huckauf et al (22) suggested a similar effect in patients with left heart failure receiving DA infusion. Thus these catecholamines could potentially be opening IPAVA; however, their role and mechanism of action in opening IPAVA in healthy humans is unknown.…”
mentioning
confidence: 99%
“…the spo 2 enhanced of about 2% along the anaesthesia session and this effect might be referred to the potent peripheral alpha receptor antagonism induced by the tranquilizer aCe. in effect aCe, a central dopaminergic receptor blocker at level of basal ganglia, forebrain, chemoreceptor trigger zone and hypothalamus, could improve the arterial oxygenation by inducing vasorelaxation in the pulmonary vascular bed and by reducing the pulmonary arteriovenous shunt in swine as previously suggested for different species [5,9,45]. in fact, it was demonstrated that during anaesthesia, the impaired arterial oxygenation can be attributed to an increased shunt and ventilation-perfusion ratio mismatch [45].…”
Section: Discussionmentioning
confidence: 60%